Food Insecurity and the Rising Urbanisation in Africa: Can ICT Revolution Bridge the GAP? - Isaac B. Oluwatayo; Ayodeji O. Ojo (Journal of Economics and Behavioral Studies, 2018)
The task of reducing food insecurity in Africa is very challenging. This is because of the changing conditions such as adverse climate change impacts. This study examined food insecurity, urbanisation and ICT in Africa.  The paper employed a combination of both secondary and historical information obtained from different sources (UNHCR, FAO, Mo Ibrahim Foundation etc). Analytical method used include descriptive statistics such as charts. Food security indices in Africa is alarming and disturbing. One in four people in Africa do not have access to food in adequate quantities and one in five African children are underweight. African agriculture is rendered unattractive by low productivity hence the exodus of labour from rural to urban areas. Africa is the most rapidly urbanising continent in the world with enabling factors comprising of infrastructure deficits in rural areas, dearth of employment opportunities and glamour of city life. However, Africaâ€™s urban centres are not immune to the challenges inducing rural-urban migration in the first place. In fact, youth unemployment in Africa is 6 times higher in urban areas than in rural areas. About 72percent of urban dwellers live in slums with the most of them having no access to basic amenities. These culminated in what is regarded in literature as â€˜urbanisation of povertyâ€™. Migrants are generally scapegoated as the causes of crimes, violence and even unemployment in urban areas. Therefore, they are subjected to sub-human living conditions. Information and Communication Technology (ICT) is particularly critical to the achievement of food security in Africa. This is because of the huge gap between markets and farmers which it is capable of filling. The paper therefore recommends increased but monitored investments in infrastructure in Africa in order to make rural areas more attractive and discourage rural-urban migration. There is also the need to provide favourable micro and macro-environment for businesses to grow especially in rural Africa.